Factors associated with cognition recovery among elders with mild cognitive impairment in Korea. (11th July 2014) - Kang, Y.; Kim, M.; Jung, D.; Cha, C.; Kim, M.
<x xml:space="preserve">Abstract</x> Background Of elders with mild cognitive impairment, around half recover their cognitive function at some point in time. However, very little is known about the factors that influence their cognitive change towards recovery. Aim This study evaluated the role of depression, instrumental activity of daily living and sleep quality as they affect cognition recovery among community‐dwelling elders. Methods The study follows a longitudinal comparative research design using secondary data analysis. Community‐dwelling elders with mild cognitive impairment were assessed twice with a 1‐year interval to assess their levels of cognition. Adult participants were drawn from those who visited a community health centre, were aged 65 or over and who were assessed as having MCI. Results Those with mild cognitive impairment when compared with the normal cognition group were more likely to be younger, have more education, living with their spouses and had better cognitive function at baseline assessment than other participants. Predictors for cognitive recovery among elders with mild cognitive impairment were age, depression and cognitive function at baseline assessment. Limitations Participants included only those who visit a community health centre in an urban area of Korea, so the findings may not be applicable to other elders with less mobility or who live in rural areas. Implications for nursing and health policy With the understanding that cognitive function and depression predict the recovery of mild cognitive function, nurses might be able to identify and target those older adults who are likely to achieve recovery of cognitive function. Additionally, health policy options, as suggested by the study as having the potential to improve mild cognitive impairment recovery, could include public education strategies.